2019
DOI: 10.3390/rs11070790
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns of Land Use/Land Cover Change in the Heterogeneous Coastal Region of Bangladesh between 1990 and 2017

Abstract: Although a detailed analysis of land use and land cover (LULC) change is essential in providing a greater understanding of increased human-environment interactions across the coastal region of Bangladesh, substantial challenges still exist for accurately classifying coastal LULC. This is due to the existence of high-level landscape heterogeneity and unavailability of good quality remotely sensed data. This study, the first of a kind, implemented a unique methodological approach to this challenge. Using freely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
93
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(120 citation statements)
references
References 82 publications
(97 reference statements)
3
93
0
1
Order By: Relevance
“…Bangladesh is a deltaic and agro-economy based developing country with a very high population density and one of the most vulnerable to disaster risks [14][15][16][17]. However, over the last decade, the economic growth of Bangladesh has skyrocketed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bangladesh is a deltaic and agro-economy based developing country with a very high population density and one of the most vulnerable to disaster risks [14][15][16][17]. However, over the last decade, the economic growth of Bangladesh has skyrocketed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bangladesh is now one of the fastest economic growth countries in the Asian region [18]. Hence, as a result of rapid economic activity along with high population pressure and environmental degradation, LULC in Bangladesh has changed very rapidly [15,16]. Empirical investigations [8,14,15,[19][20][21][22][23] have shown that along with factors like rapid population growth and economic development, land degradation, and sea-level rise are some of the other driving forces in the coastal region of Bangladesh that have led to rapid LULC transformations over different periods, and that these have been arguably more widespread and intense than in any other areas of the globe, and that these conditions continue to worsen, leading to ongoing degradation and damages in the ecological value of these vulnerable environments [8,20,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, agricultural occupation and urban expansion were verified as the two main causes of ecological land loss, as well as elevated risks. In light of the current situation, measures such as policy adjustment and ecological restoration should be taken to avoid risk and optimize land use.Previous studies have measured regional ecological security and detected its influencing factors in view of multi-scale and multi-source data [13][14][15]. Jackson et al evaluated the ecological vulnerability caused by land use changes and economic development in the U.S. Mid-Atlantic region by overlaying the maps of land-use change projections and sensitive ecological resources [16].…”
mentioning
confidence: 99%
“…Previous studies have measured regional ecological security and detected its influencing factors in view of multi-scale and multi-source data [13][14][15]. Jackson et al evaluated the ecological vulnerability caused by land use changes and economic development in the U.S. Mid-Atlantic region by overlaying the maps of land-use change projections and sensitive ecological resources [16].…”
mentioning
confidence: 99%